Analisis Perilaku Konsumen Pada Online Shopping Tokopedia Di Kalangan Mahasiswa - Ginting S, Charisma Kuriata (PESHUM : Jurnal Pendidikan, Sosial dan Humaniora, 2025)
The success of the online commerce system (e-commerce) in Indonesia cannot be separated from the enthusiasm of the people of Indonesia, who crave shopping. Tokopedia is one of the best online stores in the homeland that comes with the concept of a complete product and the ease of shopping online message across. Within fifteen years, Tokopedia has become the largest online store in Indonesia. In today's economic conditions, marketing activities in online shopping have a role to play in accordance with the function of marketing, which is one of the principal functions that must be performed by the company to be able to grow and get maximum profit. Tokopedia, as an online shopping company, is given the important role of consumer attitude in making decisions to meet the needs and desires in order to be satisfied. The purpose of this study was to analyze consumption. The population in this study is unknown. Thus, the number of samples of this research was 384 people, the students around Universitas Quality Medan. The data used are primary data. Data collected by interviews and analyzed using the Fishbein attitude analysis method and tested different attitudes. Overall results showed that consumer attitudes do not use online shopping on Tokopedia, and consumers who are using online shopping Tokopedia has a pretty good attitude towards these attributes—the attributes that exist in Tokopedia. And on some attributes of consumer attitudes, they have, on average, a good attitude as on the attributes of price, ease of access to shopping, and delivery. The result of the difference between the attitude of consumers who do not use online shopping on Tokopedia and consumers who are using online shopping Tokopedia shows that there are significant differences in the attributes studied.